Including the own fields of quantum emitters in describing generation regimes - Kuklin, V.M.; Poklonskiy, E.V. (Problems of Atomic Science and Technology, 2023)
The paper discusses three different modes of electromagnetic field generation by an ensemble of quantum emitters placed at the radiation wavelength in the one-dimensional case. The excitation of the resonator field is considered, which, as a rule, is determined by the geometry of the system, with and without taking into account the eigenfields of the emitters. The superradiance mode of the same ensemble of emitters is also analyzed. Since the main indicator of generation is the level of energy output from the system, the position of the maximum of this indicator determines the operating point of the device. Taking into account the intrinsic field of the emitters enhances the generation intensity and significantly changes the position of the operating point.